1997
DOI: 10.1099/00221287-143-11-3473
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa in cystic fibrosis: role of mucC in the regulation of alginate production and stress sensitivity

Abstract: Alginate production in Pseudomonas aeruginosa and the associated mucoid phenotype of isolates from cystic fibrosis patients are under the control of the a/gU mudBCD cluster. This group of genes encodes AlgU, the P. aeruginosa equivalent of the extreme heat shock a factor aE in Gram-negative bacteria, the AlgU-cognate anti-a factor MucA, the periplasmic protein MucB and a serine protease homologue, MucD. While m u d , mucB or mucD act as negative regulators of AIgU, the function of mucC is not known. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 39 publications
0
54
1
Order By: Relevance
“…The regulation of alginate is mediated by a hierarchy of proteins, including those encoded by the algTmucABCD operon. The mucC gene encodes a negative regulator for alginate biosynthesis (8,46), and its expression was found here to be surface induced in P. putida.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of alginate is mediated by a hierarchy of proteins, including those encoded by the algTmucABCD operon. The mucC gene encodes a negative regulator for alginate biosynthesis (8,46), and its expression was found here to be surface induced in P. putida.…”
Section: Discussionmentioning
confidence: 99%
“…MucB is also a negative regulator that binds to MucA and forms a signal transduction complex that normally keeps the AlgT transcriptional activity low Mathee et al, 1997;Rowen & Deretic, 2000). The function of MucC is generally unknown but it has been reported as being both a positive and a negative regulator (Boucher et al, 1997a). MucD is a close homologue of Escherichia coli HtrA (DegP), a periplasmic serine protease that is involved in the proteolysis of abnormal proteins and is required for resistance to oxidative and heat stress (Boucher et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…One alginate regulatory system involves the MucA, MucB, MucC, and MucD proteins (6,36,38,51) and their regulation of the sigma factor AlgU (AlgT) (27,37,61). Two studies examining clinical CF isolates from different locations found that a large percentage of the mucoid strains had mucA mutations.…”
mentioning
confidence: 99%